Hypertriglyceridemia and Its Association with HbA1c Test: A Prospective In Vivo Controlled Study. (12th February 2019) - Rodriguez-Gutierrez, Rene; Mancillas-Adame, Leonardo G.; Rodríguez-Tamez, Giselle; Diaz Gonzalez-Colmenero, Alejandro; Solis-Pacheco, Ricardo Cesar; Elizondo-Plazas, Ana Sofia; Santos-Santillana, Karla M.; Gonzalez-Sariñana, Linda; Gonzalez-Nava, Victoria; Gonzalez-Gonzalez, José Gerardo
Abstract : Background . Hypertriglyceridemia and hyperglycemia coexist in 30-60% of patients with diabetes. The impact of hypertriglyceridemia regarding HbA1c assay reliability remains uncertain. Therefore, we conducted a prospective in vivo controlled study with the aim of defining the association between triglyceride levels and HbA1c. Methods . A total of 44 patients with an index-hospital admission diagnosis of diabetic ketoacidosis or hypertriglyceridemia-induced pancreatitis, as a model for acute elevation of triglycerides, were recruited. Blood samples were drawn for the measurement of HbA1c, triglycerides, glucose, and hemoglobin at baseline and subsequently 24 and 48 hours after admission. HbA1c analysis was performed with high-performance liquid chromatography Bio-Rad D10 (NGSP approved). Results . All patients completed the study protocol. A difference between mean triglycerides from day 0 (baseline) to day 2 of 1567.2 mg/dL was observed. We found a difference between mean serum HbA1c from days 0 to 2 of 0.09% [1 mmol/mol] (p = 0.004 ). Moreover, a weak correlation between the mean difference of HbA1c and triglycerides from baseline to day 2 was found to be statistically significant (r = 0.256, p = 0.015 ). None of these findings, however, are clinically significant. Conclusion . Triglycerides do not impair the interpretation of HbA1c assay. Patients and clinicians can now be confident that hypertriglyceridemia is not an important factor when interpreting HbA1c results.